A comparison of DNA extraction methods for high‐throughput DNA analyses. (16th November 2016) - Schiebelhut, Lauren M.; Abboud, Sarah S.; Gómez Daglio, Liza E.; Swift, Holly F.; Dawson, Michael N
Abstract: The inclusion of next‐generation sequencing technologies in population genetic and phylogenetic studies has elevated the need to balance time and cost of DNA extraction without compromising DNA quality. We tested eight extraction methods – ranging from low‐ to high‐throughput techniques – and eight phyla: Annelida, Arthropoda, Cnidaria, Chordata, Echinodermata, Mollusca, Ochrophyta and Porifera. We assessed DNA yield, purity, efficacy and cost of each method. Extraction efficacy was quantified using the proportion of successful polymerase chain reaction (PCR) amplification of two molecular markers for metazoans (mitochondrial COI and nuclear histone 3) and one for Ochrophyta (mitochondrial nad6) at four time points – 0.5, 1, 2 and 3 years following extraction. DNA yield and purity were quantified using NanoDrop absorbance ratios. Cost was estimated in terms of time and material expense. Results show differences in DNA yield, purity and PCR success between extraction methods and that performance also varied by taxon. The traditional time‐intensive, low‐throughput CTAB phenol–chloroform extraction performed well across taxa, but other methods also performed well and provide the opportunity to reduce time spent at the bench and increase throughput.